2015
DOI: 10.1007/s12017-015-8363-9
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Transcriptome from the Mecp2308-Truncated Mouse Model of Rett Syndrome

Abstract: Mutations in the gene encoding the transcriptional modulator methyl-CpG binding protein 2 (MeCP2) are responsible for the neurodevelopmental disorder Rett syndrome which is one of the most frequent sources of intellectual disability in women. Recent studies showed that loss of Mecp2 in astrocytes contributes to Rett-like symptoms and restoration of Mecp2 can rescue some of these defects. The goal of this work is to compare gene expression profiles of wild-type and mutant astrocytes from Mecp2(308/y) mice (B6.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…Most studies were conducted in males, with two exclusively in females (Bedogni et al, ; Zhao et al, ), and one study using both genders (Johnson et al, ). The studies were mostly carried out using knockout mice (null), with a small proportion in Mecp2 ‐knock in mice ( Mecp 2 R270X , Mecp 2 G273X , Mecp 2 308 , Mecp 2 T158A‐Tavi , and Mecp 2 R106W‐Tavi ) (Baker et al, ; Delepine et al, ; Gabel et al, ; Johnson et al, ), and Mecp2 overexpressing mice (Tg) (Ben‐Shachar, Chahrour, Thaller, Shaw, & Zoghbi, ; Chahrour et al, ; Chen et al, ; Samaco et al, ).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were conducted in males, with two exclusively in females (Bedogni et al, ; Zhao et al, ), and one study using both genders (Johnson et al, ). The studies were mostly carried out using knockout mice (null), with a small proportion in Mecp2 ‐knock in mice ( Mecp 2 R270X , Mecp 2 G273X , Mecp 2 308 , Mecp 2 T158A‐Tavi , and Mecp 2 R106W‐Tavi ) (Baker et al, ; Delepine et al, ; Gabel et al, ; Johnson et al, ), and Mecp2 overexpressing mice (Tg) (Ben‐Shachar, Chahrour, Thaller, Shaw, & Zoghbi, ; Chahrour et al, ; Chen et al, ; Samaco et al, ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies used a combination of four distinct neuronal cell populations including thick tufted pyramidal neurons from the motor cortex, fast‐spiking parvalbumin‐positive interneurons from the motor cortex, noradrenergic locus coeruleus neurons, and cerebellar Purkinje cells (Ehrhart et al, ; Sugino et al, ). Other studies used astrocytes (Delepine et al, ; Yasui et al, ) and microglia and peritoneal macrophages (Cronk et al, ), while others used cardiovascular progenitor cells (Hara et al, ) and cortical callosal projection neurons (Kishi et al, ). Studies using cell sources not originating from brain regions include the use of fibroblasts (Orlic‐Milacic et al, ), skeletal muscle (Gold et al, ), and blood (Sanfeliu et al, ).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Nr2f2 signaling is capable of repressing parvalbumin‐expressing interneuron fate specification (Hu et al, ), which is in agreement with deficits often being found in this specific population in humans, in the form of cell loss (Zamecnik et al, ) or ectopic overabundance (Kuchukhidze et al, ). There is also the possibility of other cellular populations being affected by Nr2f2 dysregulation, as this factor has also recently been identified in astrocytes from methyl‐CpG binding protein 2 ( Mecp2 ) deficient mice, a model of Rett's syndrome (Delépine et al, ). On a similar note, Rfx3 ‐deficient mice belong to a family of animal models of primary ciliopathies, resulting in agenesis of the corpus callosum, albeit with only partial penetrance, which is intriguingly similar to the frequency of such abnormalities reported by our group previously in rats irradiated at E13 (Edwards et al, ; Kielbinski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple groups have performed transcriptome-level analysis of astrocytes from mouse models of Rett syndrome, finding significant changes in gene expression (Delepine et al, 2015;Yasui et al, 2013), and confirming Mecp2 binding to the promoters of predicted target genes via chromatin immunoprecipitation (ChIP)-seq (Yasui et al, 2013). It was also demonstrated that Mecp2-null astrocytes have abnormal glutamate clearance (Okabe et al, 2012), a finding that has also been observed in Mecp2-null microglia (Maezawa and Jin, 2010), and which may have direct effects on neurons.…”
Section: The Role Of Mecp2 In Astrocytes and Oligodendrocytesmentioning
confidence: 80%